1980
DOI: 10.1210/jcem-51-1-173
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Normal Menstrual Cycle in Kallman's Syndrome by Pulsatile Administration of Luteinizing Hormone-Releasing Hormone (Lhrh)

Abstract: The administration of small doses of LHRH at 2-hourly intervals over a 27 day period to a 24-year old patient with Kallman's syndrome resulted in ovulation as indicated by: (1) a biphasic temperature response, (2) anatomical changes in the ovaries demonstrated by ultrasound, and (3) the pattern of circulating gonadotropin and gonadal steroid concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(95 citation statements)
references
References 19 publications
3
90
0
2
Order By: Relevance
“…231 GnRH can be administered at different pulse frequencies across the cycle, mimicking physiological ovarian stimulation. 232 Alternatively, pulsatile GnRH at a constant frequency also induces maturation of ovarian follicles and triggers an LH peak. The usual doses comprise 3-10 μg per pulse, injected subcutaneously every 90 min.…”
Section: Induction Of Female Sexual Characteristicsmentioning
confidence: 99%
“…231 GnRH can be administered at different pulse frequencies across the cycle, mimicking physiological ovarian stimulation. 232 Alternatively, pulsatile GnRH at a constant frequency also induces maturation of ovarian follicles and triggers an LH peak. The usual doses comprise 3-10 μg per pulse, injected subcutaneously every 90 min.…”
Section: Induction Of Female Sexual Characteristicsmentioning
confidence: 99%
“…Pulsatile gonadotropin releasing hormone (GnRH) treatment is an appropriate and effective way to establish normal ovarian function [Crowley and McArthur 1980]. But many patients display psychological problems and are agitated by having to carry an electronic pump on their body for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent studies have demonstrated that the frequency of GnRH stimulation may itself be a critical determinant of the pituitary response to GnRH. Whereas physiological frequencies of GnRH stimulation maintain normal gonadotropin secretion in GnRH-deficient animals (1, 10, 11) and humans (12)(13)(14)(15), supraphysiological frequencies of GnRH administration produce pituitary desensitization (1,10,(16)(17)(18). In contrast, slow frequencies of GnRH stimulation increase the amplitude ofthe LH pulse in GnRH-deficient animals (10,11,19).…”
Section: Introductionmentioning
confidence: 99%